ANALISIS MANAJEMEN LAYANAN KELUHAN PASIEN TERHADAP KUALITAS LAYANAN KESEHATAN DI RSUD. AM. PARIKESIT TENGGARONG - Lina Marliana (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
The purpose of this research is to know the governance of patient complaints against the quality of medical services in RSUD. A. M. Parekesit Tenggarong Kutai Kartanegara Regency Opposite. This research uses descriptive qualitative research methods. The results showed that the governance of the patient in RSUD. A.M. Parikesit Tenggarong already well managed in accordance with the basic principles of Good Governance, namely Transparency Accountability, Corporate responsibility, Independence, and Equality and Fairness.